The rotation of preoperative-presumed lowest instrumented vertebra: Is it a risk factor for distal adding-on in Lenke 1A/2A curve treated with selective thoracic fusion? - He, Zhong; Qin, Xiaodong; Yin, Rui; Liu, Zhen; Qian, Bangping; Qiu, Yong; Zhu, Zezhang (European spine journal, 2020)
Purpose To investigate whether the rotation of preoperative-presumed lowest instrumented vertebra (LIV) is a risk factor for adding-on (AO) in adolescent idiopathic scoliosis (AIS) treated with selective posterior thoracic fusion (sPTF). Methods A total of 196 AIS patients of Lenke type 1A or 2A with minimum 2-year follow-up after sPTF with all pedicle screw instrumentation were included. Radiographical parameters were measured as follows: preoperative rotation angle of presumed LIV and LIV + 1, LIV + 1/LIV rotation difference, postoperative rotation angle of LIV and LIV derotation angle on CT scans. Patients were classified into AO group and non-AO group during the follow-up. The parameters were compared between the two groups to investigate risk factors for AO. Results Among 196 patients, 40 (20.4%) patients developed with AO at the final follow-up. Compared with non-AO group, patients with AO had significantly larger preoperative rotation angle of presumed LIV (8.8° ± 3.4° vs. 3.4° ± 2.9°, P < 0.001) and LIV + 1 (5.9° ± 4.0° vs. 3.6° ± 2.9°, P = 0.004), LIV + 1/LIV rotation difference (− 2.6° ± 3.7° vs. 0.6° ± 3.2°, P < 0.001) and postoperative rotation angle of LIV (7.2° ± 4.3° vs. 3.0° ± 2.9°, P < 0.001). The last substantially touched vertebrae (LSTV) was selected as LIV in 148 patients, among which the above described parameters were found to be remarkably larger in AO group than non-AO group as well. Multivariate analysis presented Risser grade and preoperative rotation angle of presumed LIV as independent predictors of AO. Conclusion AIS patients with low Risser grade and large preoperative rotation angle of presumed LIV are more likely to develop with AO after sPTF. Moreover, for the patients with LSTV selected as LIV, preoperative rotation of presumed LIV might be still a risk factor associated with the occurrence of AO. Level of Evidence III Graphic abstract These slides can be retrieved under Electronic Supplementary Material.